Throwing in the deep end: athletes, coaches and support staff experiences, perceptions and beliefs of upper limb injuries and training load in elite women's water polo. Issue 1 (8th March 2022) - King, Marguerite Helen; Costa, Nathalia; Lewis, Amy; Watson, Kate; Vicenzino, Bill
Abstract : To understand elite athlete, coach and support staff experiences, perceptions and beliefs in women's water polo with managing upper limb injuries and monitoring training loads. Inductive qualitative design. Twenty athletes, coaches and support staff were purposively recruited and participated in semistructured interviews. Participants either had experienced an upper limb injury or had experience managing athletes with upper limb injuries. Interviews were conducted in-person or virtually, audio-recorded, deidentified, transcribed verbatim and cleaned to ensure accuracy. Data were thematically analysed. Analysis identified five cohesive themes: (1) upper limb injury management is adequate—but prevention, communication and knowledge need improving, (2) current training load monitoring generates uncertainty and lack of consistency of processes—due to reliance on internal, and lack of external load monitoring, (3) optimal training load monitoring requires objective measurement of training load—that accurately measures the external load of athletes' upper limbs, (4) athlete-centred philosophy matters—including athlete-centred care to facilitate individually tailored rehabilitation programmes and their inclusion in management decisions, (5) mental, social and emotional aspects of upper limb injury management matter—acknowledging feelings of loss of team inclusion, fear of missing out and frustration felt by athletes as well as the emotional labour felt by coaches when supporting athletes with an upper limb injury. Upper limb injury management and training load monitoring are evolving areas where objective measurement of training load may assist in increasing consistency of communication, collaboration and coordination between all stakeholders, and to address uncertainty. Stakeholders placed value in intangible qualities such as trust and care in their relationships with other collaborators—facilitating athlete physical, mental and emotional recovery following upper limb injuries.